RANCANG BANGUN MODUL 3 PRAKTIKUM SISTEM EMBEDDED BERBASIS RASPBERRY PI (PERCOBAAN 3: PENGONTROLAN LAMPU MELALUI APLIKASI ANDROID) - Kusumo Wahid, Hindro; Rahardjo, Pratolo; Jasa, Lie (Jurnal SPEKTRUM; Vol 8 No 3 (2021): Jurnal SPEKTRUM, 2021)
The role of university in supporting embedded system development and Internet Of Things implementation seen with Embedded System + Lab Course in Electrical Engineering Study Porgram, Engineering Faculty, Udayana University. Embedded System + Lab Course is a new course, so it’s not available yet learning tools in the terms of supporting the course, then it is necessary to create Embedded System Practicum Module. Embedded System Practicum Module cosists of 4 kinds of experiment. 1st experiment: monitoring servo motor arm position change with PIR sensor in Android application. 2nd experiment: monitoring servo motor arm position change with ultrasonic sensor in Android application. 3rd experiment: controlling and monitoring light bulb with Android application. 4th experiment: controlling and monitoring light bulb with Telegram Bot. Given the many results of the discussion of experiments and subexperiments in module 3, in this article, only experimental data 3 data will be discussed. Experimental data in 3rd module showing the success of tool performance and output data suitability of monitoring and controlling lamp load status on Python Shell, Firebase and Android application. Can be concluded in this research that the success of making 3rd Module Embedded System Practicum(3rd Experiment : Lamp Controlling Through Android Application) has worked well. The overall experimental data can show the success of parsing JSON data on the Python Shell platform, Firebase database, Android application.